Development of Writing Skills for Foreign Languanges Classes - Ruzimurodova Zarina; Urokova Gulrukhsor; Uralova Charos (International Consortium of Education and Culture Research Studies, 2019)
This article is devoted to training issues of writing as an aim of teaching. The author considers the characteristic and classification of writing suggested by the majority of scientists.